Mechanism of Pd(II) Catalysis in Ce(IV) Oxidation of Amines in Acidic Medium - Kumar Singh, Ashish; Jaiswal, Jaya; Singh, R.A.; Singh, Kamini (Asian Journal of Chemistry, 2010)
Palladium(II) catalyzed oxidation of methyl amine and ethyl amine by Ce(IV) in perchloric acid has been found to be acid dependent. The reaction exhibited first-order kinetics in each of Ce(IV) and Pd(II). First order kinetics in amines in lower concentration range shifts to zero order at their higher concentrations. Negative effects of [H+], [Cl–] and μ (ionic strength) variations on the rate of reaction were observed. Pd(II), catalysis of Ce(IV)-amine reaction is explained in terms of a 1:1 complex formation between Pd(II) species and amine. The complex formed is hydrolyzed and the hydrolyzed species later reacts with Ce(IV) to give the products, namely, ammonia and the corresponding aldehyde.